Så tyk som en drengs lem – om penisattrapper, (alt for store) klitorisser og kønsforskelle i tidligt moderne livsvidenskaber - Jelved Kennild, Sidsel (Slagmark - Tidsskrift for idéhistorie, 2019)
ARE ALL WOMEN HERMAPHRODITES? ON PENIS DUMMIES, CLITORISES AND SEX DIFFERENCES IN EARLY MODERN ANATOMY This article shows how the clitoris as an anatomical discovery throughout the early modern period was debated, represented and conceptualized in the life sciences both as an anatomical object and as an emblem of (digressing) sex difference, linking theories on generation and the parts of generation. The anatomical explorations of the body and the parts of generation were paramount for answering the questions of generation, but also for procuring the empirical foundations for theories on bodily matter. As well as showcasing corporeal ontologies different from our contemporary ones, the goal is to convey the scientific explanations for the clitoris as a bodily structure and the significances it carried within the early modern life sciences. My reading is preoccupied with the importance of the natural philosophical answers to some of the corporeal questions that the clitoris raised. In a way, this runs counter to sociopolitical readings of the history of the body that sometimes fail to sufficiently account for the engagement with the warm, wet and born characteristics of the body.